2018
DOI: 10.1002/esp.4387
|View full text |Cite
|
Sign up to set email alerts
|

Seismic characterization of hyperconcentrated flows in a volcanic environment

Abstract: We present direct observations and monitoring data of a hyperconcentrated flow that occurred along La Lumbre ravine, one of the most active channels of Volcán de Colima in Mexico. Flow properties were inferred from video images and seismic data recorded by a geophone installed outside the channel. We collected flow samples 400 m upstream from the monitoring station and analyzed the variation of sediment concentration and grain-size distribution over time. A joint analysis of hydrological (i.e. flow velocity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 68 publications
(102 reference statements)
1
52
0
Order By: Relevance
“…4). The initial water flow rapidly evolved in a hyperconcentrated flow (Coviello et al, 2018) and several front waves were observed during flooding (I and II, Fig. 8b) for which an average flow discharge of 80-100 m 3 s −1 was estimated, and two main pulses arrived at 23:30 and 00:00 (24 October), with 6 m depth block-rich fronts and maximum flow discharges of 900 m 3 s −1 (III, IV, V and VI, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). The initial water flow rapidly evolved in a hyperconcentrated flow (Coviello et al, 2018) and several front waves were observed during flooding (I and II, Fig. 8b) for which an average flow discharge of 80-100 m 3 s −1 was estimated, and two main pulses arrived at 23:30 and 00:00 (24 October), with 6 m depth block-rich fronts and maximum flow discharges of 900 m 3 s −1 (III, IV, V and VI, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). Both stations consist of a 12 m high tower with a directional antenna transmitting data in real time to RESCO facilities, a camcorder recording images every 2-4 s with a 704 × 480 pixel resolution, a rain gauge coupled with a soil moisture sensor and a 10 Hz geophone (Vázquez et al, 2016a;Coviello et al, 2018). (Table 1).…”
Section: Lahar Monitoring At Volcán De Colimamentioning
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with the estimations made by Berrocal et al () of the seismic energy released by the large Mantaro landslide (complex rockslide, volume of 1.3 km 3 , surface wave magnitude M S = 4.1), which is about 0.01% of the kinetic energy, which is in turn about 1% of the potential gravitational energy. Boulder‐rich fronts are the dominant seismic source of debris flows (Coviello et al, ; Turowski et al, ; Vázquez et al, ). Length and mass distribution within a debris flow wave do not change over time scales; consequently, different amplitudes are due to either different front‐receiver distances or different kinetic energy values.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm parameters would probably need a refinement to be adapted to local conditions (channel geometry, flow rate, and distance between sensors). Furthermore, flow rheology has a strong impact on the propagation of ground vibrations through the landslide body (Bertello et al, ), and a large, slow‐moving debris flow can be seismically quieter than a much smaller, fast‐moving hyperconcentrated flow (Coviello et al, ). In this context, other monitoring data would be precious to characterize both debris flow processes and other possible sources of false alarms in a channel where an operational EWS is needed, especially at a first stage when the monitoring data set is small.…”
Section: Discussionmentioning
confidence: 99%